Indicadores de sustentabilidade da produção orgânica na agricultura familiar do sudoeste do Paraná - Feitosa Filho, Luiz Alves (2018)
The contemporary debates about the crisis of the world economic model impulsioned the construction of the concept of the sustainability, which integrates three essential dimensions: social, economic and environmental. The objective of this study is to select indicators of the social, economic and environmental sustainability in organic production systems and to analyze the selected indicators taking in consideration the principles of sustainability, was accomplish in 28 Family Production Units (FPUs) of four counties ( Capanema, Planalto, Perola do Oeste and Saltra do Lontra) in the Southwest of the Paraná, in the social, economic, and environmental dimensions. The methodological script for conducting the research is based on a descriptive case study, the deductive method, together with the applied research of quantitative, qualitative, exploratory and bibliographic character, with application of the semistructured questionnaire with open and closed questions. The questionnaire is a data collection system that obtains information directly from the interviewee, is a list of questions that will be annotated by the interviewer. In the social dimension, analyzed indicators related to schooling, health, housing, family succession, rural exodus and degree of satisfaction in the development of organic production activity. In the economic dimension, were analyzed the rural retirement, financial resources of the family, structure used in the production process (buildings, machinery and equipment, land and labor) of the property, cultures produced, cost production, channels and prices commercialization. In the environmental dimension, were analyzed indicators related to soil, water and forests. In this analysis, also were analyzed environmental aspects related to sanitation, domestic trash and animal waste management. From the analysis of the information collected, it is concluded that in the social aspect, it is necessary the adhesion of strategies for the strengthening of family succession, because a significant percentage of the children of the interviewees left the properties studied in reason study and wedding; in the economic aspect, the issue of the organic food prices and access to credit are fundamental; in the environment aspect is necessary to fully adjust environmental aspects in accordance with current environmental legislation to strengthen the organic production activity.